EXAMINING LIFE EXPECTANCY PATTERNS BY REGION, COUNTRY, AND GENDER IN AFRICA - Alfred Ayo Ayenigba; Abraham Soji Taiwo (Parameter: Journal of Statistics, 2026)
This study examines life expectancy patterns across 54 African countries, utilizing secondary data from the World Health Organization (WHO) and Statista. Employing descriptive statistics, a paired sample t-test, and a Wilcoxon signed-rank test, the analysis reveals pronounced regional disparities: North Africa records the highest average life expectancy (73.2 years), followed by Southern Africa (65.9 years), East Africa (64.1 years), West Africa (63.3 years), and Central Africa (61.9 years). A statistically significant female longevity advantage of 4.40 years (t = 19.18, p < 0.001; Wilcoxon Z = 6.1, p < 0.001) is observed consistently across all regions, with the widest gender gap in Southern Africa (6.2 years) and the narrowest in East Africa. Eritrea is a notable anomaly, where male life expectancy marginally exceeds female by 0.3 years. These findings underscore the need for gender-sensitive health policies and targeted regional interventions to address persistent health inequities across Africa.